2010
DOI: 10.1021/jf1034114
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Caper (Capparis spinosa L.) Fruit Aqueous Extract and the Isolation of Main Phytochemicals

Abstract: Caper (Capparis spinosa L.) fruits have been used as food as well as folk medicine in the treatment of inflammatory disorders, such as rheumatism. The present study was carried out to study the anti-inflammatory activities of C. spinosa L. fruit (CSF) aqueous extract and to isolate main phytochemicals from its bioactive fractions. The CSF aqueous extract were separated into three fractions (CSF1-CSF3) by macroporous adsorption resins. The fractions CSF2 and CSF3 effectively inhibited the carrageenan-induced pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 27 publications
1
74
0
1
Order By: Relevance
“…Phenolics: rutin, tocopherols, carotenoids, and vitamin C [97]. Flavonoids, indoles, and phenolic acids [98] Potent antihyperglycemic activity in STZ rats without affecting basal plasma insulin concentrations [99]. Hypoglycemic activity [95] Tertiary and quaternary alkaloids, glycoside and saponin components [101].…”
mentioning
confidence: 99%
“…Phenolics: rutin, tocopherols, carotenoids, and vitamin C [97]. Flavonoids, indoles, and phenolic acids [98] Potent antihyperglycemic activity in STZ rats without affecting basal plasma insulin concentrations [99]. Hypoglycemic activity [95] Tertiary and quaternary alkaloids, glycoside and saponin components [101].…”
mentioning
confidence: 99%
“…Moreover, a direct relationship between persistent pain and oxidative stress has been demonstrated (Di Cesare Mannelli et al, 2012). Several authors suggested the relevance of the anti-oxidant effects of quercetin and other flavonoids in the pain reliever properties of Capparis spinosa fruit extracts (Feng et al, 2011;Zhou et al, 2010). Furthermore, flowering buds of Capparis spinosa can counteract necrosis of chondrocytes and trigger lowering of NO synthase and oxygen radicals in an in vitro model of articular damage (Panico et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Al-Said et al, 1988;Sher and Alyemeni, 2010) reported that, in traditional medicine, infusions made from caper are considered to be beneficial for the treatment of rheumatism, gout and abdominal pains; moreover, pastes are used for topic applications to treat swollen joints, skin rashes and burns (Eddouks et al, 2004;Inocencio et al, 2002). The anti-nociceptive and anti-inflammatory properties of Capparis are described in different animal models (Arslan et al, 2010;Zhou et al, 2010). In particular, flowering buds and fruits of Capparis spinosa have shown significant anti-inflammatory and anti-oxidant effects in both in vivo and in vitro model of articular damage (Feng et al, 2011;Panico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The constituents of C. spinosa include the saccharides and glycosides, flavonoids, alkaloids, terpenoids and volatile oils, fatty acids and steroids [33]. The major compounds found in C. spinosa are flavonoids, indoles, and phenolic acids [21]. Interestingly, a study has revealed the presence of both α-and γ-tocopherol in buds of C. spinosa as well as an appreciable level of vitamin C [20].…”
Section: Phytochemistrymentioning
confidence: 99%
“…The important presence of alpha tocopherol in the caper parts makes a new choice for protecting cell membranes from oxidative damage [19,20]. Cappariside is one of new antioxidant isolated from the C. spinosa fruit [19]; this cappariside (4-hydroxy-5-methylfuran-3-carboxylic acid) can be used against multiple types of cancer cells [21]. Similarly more than eleven organic acids isolated from C. spinosa possess similar beneficial effects.…”
Section: Antioxidant Anti-allergic and Anti-inflammatory Activitiesmentioning
confidence: 99%